Twelve formyl phloroglucinol meroterpenoids from the leaves of Eucalyptus robusta. (July 2019) - Shang, Zhi-Chun; Han, Chao; Xu, Jia-Li; Liu, Rui-Huan; Yin, Yong; Wang, Xiao-Bing; Yang, Ming-Hua; Kong, Ling-Yi
Abstract: Twelve formyl phloroglucinol meroterpenoids (FPMs) were isolated from the leaves of Eucalyptus robusta Smith. Their structures were elucidated via spectroscopic data analysis, the circular dichroism (CD) exciton chirality method, Rh2 (OCOCF3 )4 -induced CD experiments, and application of the Snatzke chirality rules. Eucalrobusones Q, S, and X are the first FPMs that have been identified in which the C-7′ of phloroglucinol is linked to the C-15 of cadinane, the C-4 of cubebane, and the C-8 of menthane, respectively. (+)-Eucalrobusone X exhibited the most potent antifungal ability against Candida albicans with a MIC50 value of 10.78  μ g/mL, and eucalrobusone U exhibited the greatest anti- C. glabrata activity with MIC50 value of 1.53  μ g/mL. Graphical abstract: As a result of investigating antifungal formyl phloroglucinol meroterpenoids (FPMs), twelve FPMs including three undescribed carbon skeletons were isolated from the leaves of Eucalyptus robusta .Image 1 Highlights: Twelve formyl phloroglucinol meroterpenoids (FPMs) were isolated from Eucalyptus robusta. The carbon skeletons of compounds1, 3, 9, and10 are reported here for the first time. FPMs were determined by CD exciton chirality method, Rh2 (OCOCF3 )4 -induced CD experiment, and the Snatzke chirality rules. Some FPMs exhibited significant antifungal activities against Candida glabrata and C. albicans.